Influencia de la soldabilidad de un acero inoxidable austenitico - Camargo-Suarez, Ernesto; Bohórquez-Espinosa, Leonardo; Sánchez-Alarcón, Mónica Katherine (Revista Científica, 2018)
The Masa Stork Company recognized in the hydrocarbons sector in Colombia, in a power generation project saw the need to use 2-inch tubing to transport wastewater in the cooling of motor-generators, presenting the problem of fracture in the welding when they are put into operation. When stainless steels are heated in a temperature range of 500 ° C to 700 ° C, the carbon-containing the steel reacts with the chromium to form chromium carbides that do not have the same characteristics as the alloyed chromium. These reactions deplete the steel and reduce its properties in the heated zone. This investigation focused in the determination of the influence of the temperature in the ZAT of a welding in stainless steel AISI 316, under GTAW process, welded with ER316 electrode when subjected to pre-heating temperature before welding and its behavior before heat treatment; and determining that in the welding a low contribution of heat must be taken into account, distributing the heat in a balanced way so that it is distributed in the piece as symmetrically as possible. In addition, it must be ensured that the level of embrittlement is as low as possible, thus making the Zone Affected by heat more narrow.